Modular landscapes - Worthley, Simon (My University, 2025)
The United States is currently in a housing crisis due to construction costs and market demand (Stein 2019; Reuben and Lei 2010). Because of these challenges, many people have been looking into creative new ways to build houses more efficiently. The aerospace and automotive industries inspire this thinking through their manufacturing methods, where each component is precisely created and efficiently assembled in a factory and then transported where needed. Modular construction offers interchangeability, efficiency, and precision. While there have been many advancements within modular buildings, little attention has been given to integrating them into the surrounding landscape. Biophilic design is an important consideration when creating comfortable spaces for people and incorporating these designs into the surrounding context. This study utilizes modular and biophilic design strategies to understand how to make a modular landscape that integrates into the surrounding environment.
Keywords: Modular landscapes; Modular housing; Biophilia; Prefabricated housing; Reconfigurability; Cottage court